Error-tolerant multiplier for high speed application - Khaing, Yin Kyaw (2011)
With the advent of hand held computing devices that require functionality rivaling the desktop, low-power and high-performance systems have become very important. The transistor network contributes mostly to the overall power dissipation and is becoming a major obstacle in implementing those systems. Hence, the need for high performance basic sequential element with low-power dissipation is steadily growing. The aim of this project is to develop a new type of multiplier to fulfill this need. In this report, for the first time, a multiplier design concept that engages accuracy as a design parameter is proposed. By introducing accuracy as a design parameter, we can break-through the bottleneck of conventional digital IC design techniques to improve on the performances of power consumption and speed. The two dimensional trade-off between power and speed becomes three-dimensional, i.e. power-speed-accuracy. To realize the design concept, digital multiplier circuits were studied and a novel mechanism is proposed in this work. The new type of multiplier adopting the proposed mechanism is named Error-Tolerant Multiplier (also called ETM). As illustration, the designs of 8-bit and 12-bit Error-Tolerant Multiplier, taken as examples, are described to elaborate on the design process and detailed circuit implementation of an ETM.